Lactylation: The emerging frontier in post-translational modification - Lu, Zhou; Zheng, Xueting; Shi, Mingsong; Yin, Yuan; Liang, Yuanyuan; Zou, Zhiyan; Ding, Chenghe; He, Yuanjing; Zhou, Yan; Li, Xiaoan (Frontiers in Genetics, 2024)
Lactate, a metabolic byproduct, has gained recognition as a highly influential signaling molecule.Lactylation, an emerging form of post-translational modification derived from lactate, plays a crucial role in numerous cellular processes such as inflammation, embryonic development, tumor proliferation, and metabolism. However, the precise molecular mechanisms through which lactylation governs these biological functions in both physiological and pathological contexts remain elusive. Hence, it is imperative to provide a comprehensive overview of lactylation in order to elucidate its significance in biological processes and establish a foundation for forthcoming investigations. This review aims to succinctly outline the process of lactylation modification and the characterization of protein lactylation across diverse organisms. Additionally, A summary of the regulatory mechanisms of lactylation in cellular processes and specific diseases is presented. Finally, this review concludes by delineating existing research gaps in lactylation and proposing primary directions for future investigations.